Keterlambatan Pelaksanaan Retensi Dokumen Rekam Medis di Rumah Sakit: Literature Review - Avid Wijaya; Fatimah Azzahro Nur Firdausiyah; Prima Soultoni Akbar (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
Retention of medical record documents in hospitals must be implemented to limit the number of documents that have been stored on storage shelves for five (five) years, so that they do not accumulate between active and inactive medical record documents. However, several variables contributed to the delay in the implementation of the medical record retention policy. The purpose of this study was to determine procedures, Standard Operating Procedures (SOP), and other factors that contributed to delays in retention of medical records in hospitals. The study was conducted with a literature review of searches on Google Scholar and Garuda. The literature data were analyzed according to the inclusion and exclusion criteria, namely through cross-sectional research methodologies, descriptive surveys, qualitative studies, and journals published between 2017 and 2021. Of all the journals that have been obtained, the procedure for implementing the retention of medical record documents in hospitals is still not implemented properly. The SOP that has been set does not fully explain the procedure for implementing the retention of medical record documents because there are no certain procedures. The delay in the implementation of retention of medical record documents in hospitals is due to differences in the characteristics of archiving officers, supporting facilities and infrastructure, and schedules for storing medical record documents. SOP is important to be made as a guideline to reduce officer errors, and there are several components that cause delays in the implementation of retention of medical record documents in hospitals.